The Lid Domain in Lipases: Structural and Functional Determinant of Enzymatic Properties - Khan, Faez Iqbal; Lan, Dongming; Durrani, Rabia; Huan, Weiqian; Zhao, Zexin; Wang, Yonghua (Frontiers in Bioengineering and Biotechnology, 2017)
Lipases are important industrial enzymes. Most of the lipases operate at lipid-water interfaces enabled by a mobile lid domain located over the active site. Lid protects the active site and hence responsible for catalytic activity. In pure aqueous media the lid is predominantly closed, whereas in the presence of a hydrophobic layer it is partially opened. Hence, the lid controls the enzyme activity. In the present review, we have classified lipases into different groups based on the structure of lid domains. It has been observed that thermostable lipases contain larger lid domains with two or more helices, whereas mesophilic lipases tend to have smaller lids in the form of a loop or a helix. Recent developments in lipase engineering addressing the lid regions are critically reviewed here. After on the dramatic changes in substrate selectivity, activity and thermostability have been reported. Furthermore, improved computational models now can rationalize these observations by relating it to the mobility of the lid domain. In this contribution, we summarized and critically evaluated the most recent developments in experimental and computational research on lipase lids.